Structural characteristics, physicochemical properties and prebiotic potential of modified dietary fibre from the basal part of bamboo shoot. (29th July 2020) - Fang, Dongya; Wang, Qi; Chen, Canhui; Li, Zhengyi; Li, Shuting; Chen, Wen; Zheng, Yafeng
Summary: The basal part of bamboo shoot is a novel resource to produce dietary fibre (BDF). However, its insolubility in water, stiff texture and low degradability limit its applicability in foods. This study explored the feasibility of improving the structural and functional properties of BDF by enzymatic hydrolysis and dynamic high‐pressure micro‐fluidisation (DHPM). Both methods are efficient to reduce the fibre particle size and caused significantly increased roughness on the fibre surface, especially for the porous structure after DHPM treatment. Crystallinity of DHPM‐modified fibres was increased from 23.01% to 33.53%, due to the disruption of lignin and hemicellulose, which was further confirmed by the FT‐IR spectra. The modified fibres exhibited significantly enhanced swelling capacity and holding water/oil capacities. Moreover, the modified fibres exhibited improved in vitro prebiotic property, which could constantly supply the carbon source and stimulate the growth of Lactobacillus acidophilus ATCC 4356 and Bifidobacterium longum ATCC 15707. Abstract : Improving the structural and functional properties of dietary fiber from bamboo shoot by enzymatic hydrolysis and dynamic high‐pressure micro‐fluidization.